The Origins of the Gospels - Walsh, Robyn Faith (Biblical archaeology review, 2022)
The article reports on the origins of the Gospels. It mentions The Gospels should be viewed as writings not outside literate culture but at its center in the first centuries C.E., the Jesus of the Gospels can be fruitfully compared with the Cynics, Aesop, the pastoral heroes of the Greek novel, or witty underdogs in the biographical tradition.